Stress and strain characteristic of stone mastic asphalt incorporating eggshell powder - Putra Jaya, Ramadhansyah; K. A., Masri; E., Ganesan; Doh, Shu Ing; S. M. Z., Nur Syafiqah; Z. F., Mohamed Jaafar; N., Mashros (IOP Publishing Ltd, 2021)
Stone mastic asphalt (SMA) is a type of gap graded asphalt mixture. Due to large difference between the gap of large and small size aggregate, this type of mixture suffers a few drawbacks such as low resistance towards permanent deformation. Thus, the usage of ecofriendly and sustainable additive is crucial in enhancing the performance of SMA. Thus, this study is utilizing various amount of eggshell powder as asphalt modifier. Among the tests involve to evaluate the stress-strain characteristic of modified SMA are Resilient Modulus Test and Dynamic Creep Test. From the test, it shows that the addition of 4% eggshell powder produces the highest value of resilient modulus and lowest value of dynamic creep for SMA. In conclusion, this study proves that the eggshell powder is capable in enhancing the performance of SMA especially in terms of permanent deformation resistance.